Banking market structure and macroeconomic stability: Are low-income countries special? - Franziska Bremus; Claudia M. Buch (Deutsche Bundesbank, 2014)
Does the structure of banking markets affect macroeconomic volatility and, if yes, is this link different in low-income countries? Banking markets in low-income countries differ from those in developed market economies. Banking systems in lower-income countries are typically smaller and less open. In this paper, we explore the channels through which the structure of banking markets affects macroeconomic volatility. Our research has three main findings. First, we study the relevance of granular effects: if the degree of market concentration in the banking sector is sufficiently high, idiosyncratic volatility at the bank-level can impact aggregate volatility. We find weak evidence for a link between granular banking sector volatility and macroeconomic fluctuations. Second, a higher share of domestic credit to GDP coincides with higher volatility in the short run. Third, a higher level of cross-border asset holdings, i.e. a higher degree of de facto financial integration, increases volatility in low-income countries.
Keywords: G21; E32; 330; bank market structure; financial integration; granularity; macroeconomic volatility; low-income countries